2013
DOI: 10.3233/jad-122215
|View full text |Cite
|
Sign up to set email alerts
|

MR Microscopy of Human Amyloid-β Deposits: Characterization of Parenchymal Amyloid, Diffuse Plaques, and Vascular Amyloid

Abstract: Cerebral deposits of amyloid-β peptides (Aβ) form the neuropathological hallmarks of Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA). In the brain, Aβ can aggregate as insoluble fibrils present in amyloid plaques and vascular amyloid, or as diffuse plaques consisting of mainly non-fibrillar Aβ. Previously, magnetic resonance imaging (MRI) has been shown to be capable of detecting individual amyloid plaques, not only via the associated iron, but also Aβ itself has been suggested to be responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Because this hydrophobicity is related to the concentration of the amyloid peptide, diffuse deposits are probably less prone to be revealed by Gd-stained MRI than compact plaques. Interestingly, previous studies have shown that diffuse deposits are not detected by MRI without contrast agents in mice 42 or in human brains 43 . Thus, it seems that Gd-stained MRI does not improve the ability to detect diffuse plaques as compared to contrast-agent free MRI.…”
Section: Discussionmentioning
confidence: 92%
“…Because this hydrophobicity is related to the concentration of the amyloid peptide, diffuse deposits are probably less prone to be revealed by Gd-stained MRI than compact plaques. Interestingly, previous studies have shown that diffuse deposits are not detected by MRI without contrast agents in mice 42 or in human brains 43 . Thus, it seems that Gd-stained MRI does not improve the ability to detect diffuse plaques as compared to contrast-agent free MRI.…”
Section: Discussionmentioning
confidence: 92%
“…Wengenack et al reported that the fast decay of transverse magnetization (T 2 *) is not solely attributed to the presence of iron within the amyloid plaques in the cortex and hippocampus in APPPS1 double transgenic mice (27). This notion was further supported by Nabuurs et al, as only fibrillar amyloid plaques rather than diffuse plaques induced significant changes in either T 2 or T 2 * values and the loss of transverse magnetization was not necessarily correlated with the presence of iron within amyloid deposits (28). We now provide further evidence that the density of the amyloid deposition is a key factor for fast transverse magnetization decay, as T 2 * signal intensity is inversely correlated with amyloid deposition density within single amyloid plaques.…”
Section: Discussionmentioning
confidence: 93%
“…An increase may also originate from susceptibility changes occurring in tissue lesions, i.e. A β and τ -tangles 83 , as pointed out by the trend between and Braak Stage shown in Fig. 2 , or be caused by microhemorrhages, or myelin changes 36 , 38 also taking place in AD 25 .…”
Section: Discussionmentioning
confidence: 98%